THE STABILITY OF PALLADIUM(II) HYDROXIDE AND HYDROXY-CHLORIDE COMPLEXES: AN EXPERIMENTAL SOLUBILITY STUDY AT 25-85OC AND 1 BAR - RECENT EXPERIMENTAL CONSTRAINTS AND A RE-EVALUATION OF THEORETICAL PREDICTIONS - van Middlesworth J.M.; Wood S.A. (My University, 1999)
Solubility methods were employed to determine conditional equilibrium constants for the formation of hydroxide and mixed hydroxy-chloride complexes of Pd(II). Measurements were made over a temperature range of 25-85°C, a pH range from 0 to 12, and ionic strengths of 0.1, 0.2, 0.5 and 1.0 molal in both KCl and NaClO4 media. Several speciation models were fit to the data using nonlinear regression, and the model yielding the best fit with the fewest number of species was accepted for each temperature and ionic strength. The conditional equilibrium constants were then fit to a function of ionic strength and temperature (including a Debye-Huckel term) to facilitate interpolation and extrapolation to infinite dilution. The following species were found to be important in KCl solutions: PdCl42-, PdCl3(OH)2-, and Pd(OH)20. The relative proportions of the species are dependent on pH and ionic strength (chloride concentration). In perchlorate media the predominant species were Pd(OH)3-, Pd(OH)20, PdOH+ and Pd2+, depending on pH. Conditional stability constants determined in this study agree well with those reported in previous work for the simple chloride and hydroxide complexes, but our results suggest that mixed complexes may be more important than previously thought, and that PdCl3(OH)2- may be the dominant species in seawater, followed by Pd(OH)20.